THE ADDITION OF VITAMIN E IN DILUENT BTS® OF VIABILITY AND MORTALITY OF SPERMATOZOA LANDRACE PIG STORED IN TEMPERATURE 15°C - Bebas, Wayan; Buyona, Geovany Larastiyani; Budiasa, Made Kota (Buletin Veteriner Udayana, 2016)
The aim of the study was to determine viability and motility spermatozoa of Landrace pigs inthe Beltsville Thawing Solution® (BTS) diluents with the addition of vitamin E (?-tokoferol) thatwas stored at a temperature 15oC for 96 hours. The form of semen used a fresh semen from themale landrace pigs two years. Semen was collected by massage method. This study used completely randomized design with four treatment groups with each are treatment I as control,treatment II with addition 300 ?g/ml Vitamin E, treatment III with addition 400 mg/ml of vitamin E and treatment IV with addition 500 mg/ml of vitamin E. Each group was repeated six times and then stored at a temperature 15oC for 96 hours. The results showed that addition of vitamin E significantly on the viability and motility spermatozoa of Landrace pigs. The addition of vitamin E 400 ?g/ml gave the preeminent of viability and motility during storage at a temperature 15oC for 96 hours. This study concluded that the addition of vitamin E 400 ?g/ml in BTS® odiluents at 15oC for 96 hours was able to increase the viability and motility spermatozoa of Landrace pigs.
Keywords: stored of spermatozoa; Landrace pig; viability; motility; vitamin E